Tectonics of the Skjálfandadjúp basin, Tjörnes Fracture Zone - Sigríður Magnúsdóttir 1983- (2013)
Divergent plate boundaries are commonly made up of individual rift segments, either parallel or oblique to the plate boundary, and linked by transform faults oriented parallel to the plate movement. The combination of the divergent plate boundary and mantle plume in Iceland results in a broad zone of deformation, with combination of divergent, transform and oblique plate boundary segments. The Tjörnes Fracture Zone, located on the coast and offshore Northern Iceland, is a complex transform zone where deformation takes place on three WNW-NW oriented seismic lineaments superimposed on N-S trending rift structures; representing the successive rift locations as the main rift zone relocated from western to eastern Iceland. In this study, the tectonic framework and Holocene evolution of the Skjálfandadjúp basin, one of the N-S oriented sediment basins of the Tjörnes Fracture Zone, was mapped using multibeam bathymetric-, high-resolution seismic reflection and tephrochronological data. The results reveal in detail the NNW oriented, asymmetrical rift basin, composed of normal faults with maximum vertical separation of 50-60 m and partly filled with post-glacial sediments. The Skjálfandadjúp basin is composed of two fault systems; an oblique system of faults having large vertical displacement, bordering a subsiding rift made up of normal faults oriented perpendicular to the plate motion. Most part of the tectonic activity observed in the sediments of the Skjálfandadjúp basin took place in early post-glacial times, cumulating in rifting episodes at 12, 11, 10 and 3 kyrs BP.